Efficacy and tolerability of certolizumab pegol in Crohn's disease in clinical practice - O V Knyazev; A V Kagramanova; A A Lishchinskaya; N G Samsonova; N V Orlova; V A Rogozina; A I Parfenov (Терапевтический архив, 2018)
Aim. To assess the efficacy and tolerance of certolizumab pegol (CP) in patients with Crohn's disease (CD) treated in the Department of inflammatory bowel diseases of the A.S. Loginov Moscow Clinical Research Center and to determine the predictors of response to therapy. Materials and methods. All patients with CD who had received the treatment of CP were observed prospectively for at least 6 months or until the date of discontinuation of the drug. The effectiveness of the study was assessed response to therapy by the 6th week, maintaining the clinical response (6th and 26th weeks), the dynamics of endoscopic parameters by the 10th and 54th week of therapy, long-term maintenance of remission, healing fistula. Used univariant and multivariate analyses of predictors of response to treatment. Results and discussion. The study included 39 patients: 12 (30.7%) men and 27 (69.3%) female, the average duration of observation was 104 weeks. The interdepartmental range was in the range from 28 to 158 weeks. Clinical improvement occurred in 38 out of 39 (97.4 %) patients with CD. Comparative analysis of response to treatment with CP have bionaive patients previously treated with another inhibitor of TNF-α. In the group of bionaive response to therapy in a month, 6 months and at the end of the observation period occurred at 100.0%, 95.0% and 95.0%, respectively. In the group of patients previously treated with GSI, the response rate was about 94.4 %, 88.9 % and 77.7% week 54 endoscopic response and endoscopic remission was maintained in 46,2% and 30,1% patients, complete healing of the mucosa on the background of maintenance therapy, CP, was preserved in 20.5% of patients with Crohn's disease. In the group of patients with perianal lesions (n=13) complete closure of all fistulas was observed in 5 (38.6 %) patients, partial response was observed in 4 patients (30,7%) patients, in 4 (30.7 %) closure of fistulas occurred. The frequency of adverse events was 0 cases (0.0%). The dose escalation was required in 3 patients (7,7%) patients with CD. Dose escalation in our study required patients with high initial CDAI and previous inefficiencies of the other two inhibitors of TNF-α. Reliable predictors of secondary loss of response and need for dose escalation of the drug has been the continued level of CRP >5 mg/l after 2 weeks initiation of therapy CP and smoking. Conclusion. The obtained results demonstrate the efficacy and tolerability profile of CP appropriate for long-term CD therapy in real clinical practice.